Takotsubo cardiomyopathy complicating a twin pregnancy at partum - Rao, B.V. Nagabhushana; Rekha, A.; Narayan, A. Sankar; Manjusha, A. (International Journal of Research in Medical Sciences, 2019)
Takotsubo cardiomyopathy is a rare syndrome characterized by acute left ventricular dysfunction with regional left ventricular ballooning, mimicking myocardial infarction. This condition is often described in post-menopausal women. Authors present a case in an elderly primi with twin gestation immediately after Cesarean surgery. We discussed her presentation, investigations, diagnosis, management and outcome. 35 year female, a primi with twin pregnancy developed chest pain and shortness of breath immediately after Cesarean surgery. Her Electrocardiograph was abnormal, and Echocardiogram demonstrated abnormal apical ballooning of the left ventricle and severe dysfunction. Cardiac enzymes were elevated and chest skiagram showed pulmonary edema. She was managed in the intensive care unit with oxygen supplementation, diuretics and inotropes. She made an excellent recovery with normalization of left ventricular ejection fraction within 8 days. During the six months follow up, she was asymptomatic and left ventricular function remained normal.